1990
DOI: 10.1144/gsl.sp.1992.049.01.19
|View full text |Cite
|
Sign up to set email alerts
|

The tectonic evolution of pre-Permian rocks, Central and Southeastern Oman Mountains

Abstract: The structural history of pre-Permian basement rocks exposed in the domal uplifts of Jebel Akhdar, Jebel Nakhl and Saih Hatat, central and southeastern Oman mountains, is dominated by Late Palaeozoic and Late Cretaceous deformation and metamorphism. In Jebel Akhdar pre-Permian rocks have been deformed by large NE-SW trending thrusts and folds and intense cleavage during Late Palaeozoic compression. Later reactivation of these structures accompanied by a major flattening deformation caused by loading may be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…The geometry of this Permian unconformity, its age compared to the rifting period, the geochemistry of associated basalts, the sedimentary record and the geodynamic context, imply a synrift thermal uplift and not a contemporaneous orogenic event, as clearly demonstrated in all these areas by thorough field work done in the last ten years (e.g. Mann & Hanna 1990;Vannay 1993;Garzanti et al 1994Garzanti et al , 1996Pillevuit et al 1997). Similarly, Ricou (1974) and Braud (1987) never spoke of Variscan deformation or metamorphism concerning the Sanandaj-Sirjan Zone (the Iranian part of the Podataksasi Zone); they regarded the metamorphic rocks of this region as a retrogressed epi-Baikalian basement [this is also indicated on the 1:1 000 000 map of Iran (Huber & Eftekhar-Nezhad 1978)].…”
Section: There Is Still Some Confusion About What Tethys Existed At Wmentioning
confidence: 88%
“…The geometry of this Permian unconformity, its age compared to the rifting period, the geochemistry of associated basalts, the sedimentary record and the geodynamic context, imply a synrift thermal uplift and not a contemporaneous orogenic event, as clearly demonstrated in all these areas by thorough field work done in the last ten years (e.g. Mann & Hanna 1990;Vannay 1993;Garzanti et al 1994Garzanti et al , 1996Pillevuit et al 1997). Similarly, Ricou (1974) and Braud (1987) never spoke of Variscan deformation or metamorphism concerning the Sanandaj-Sirjan Zone (the Iranian part of the Podataksasi Zone); they regarded the metamorphic rocks of this region as a retrogressed epi-Baikalian basement [this is also indicated on the 1:1 000 000 map of Iran (Huber & Eftekhar-Nezhad 1978)].…”
Section: There Is Still Some Confusion About What Tethys Existed At Wmentioning
confidence: 88%
“…Recently, both Michard (1982Michard ( , 1983 and Mann & Hanna (1990) studied the late Palaeozoic deformation, documenting the presence of a NE-SW trending foldbelt. In the Jebel Akhdar, Jebel Nakhl, and Saih Hatat, an intense slaty cleavage dips generally to the SW at angles between 20 ~ and 50 ~ .…”
Section: Late Palaeozoic Orogeny In Omanmentioning
confidence: 99%
“…In the Jebel Akhdar, Jebel Nakhl, and Saih Hatat, an intense slaty cleavage dips generally to the SW at angles between 20 ~ and 50 ~ . Late Cretaceous deformation in the NW part of the Saih Hatat window has overprinted and largely obscured the Late Palaeozoic structures (Mann & Hanna 1990). Stretched grain and pressure shadow orientations in the slaty cleavage plane indicates a predominant stretching direction trending S to SW. Michard (1982) indicated that fold vergence seems N and NW in many places where the cleavage/bedding relationship can be observed, and that this is commonly corroborated by parasitic fold overturning, but he also stressed that vergence of late Palaeozoic folds is inconsistent, as, locally, are the trends of fold axial traces.…”
Section: Late Palaeozoic Orogeny In Omanmentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ continental margin exhibits a variably complete Late Precambrian-Early Palaeozoic prerift sedimentary sequence that was unconformably overlain by a Late Permian transgressive succession, beginning with thin clastics and passing directly into much thicker shallow-marine carbonates (Glennie et al 1973;Rabu et al 1990). The unconformity was exploited as a Late Cretaceous emplacement related thrust in some areas, whereas in others a spectacular angular unconformity is exposed (Mann & Hanna 1990). The underlying Pre-Permian sequence is deformed, cleaved and folded and was subjected to regional low-grade metamorphism in contrast to the overlying Upper Permian and younger sequence.…”
Section: Oman Rifted Marginmentioning
confidence: 99%